Walking in a straight line–the early detection of cardiomyopathy by the general physician. (14th October 2021) - Ker, J
Abstract: Introduction: The orientation of muscle fibers in the left ventricle is sophisticated. This peculiar orientation causes the left ventricle to contract in three directions–longitudinal, radial and circumferential. Normal myocardial mechanics is essential for systolic and diastolic function. For the clinician an impairment in longitudinal function is of utmost importance, as it has been shown to be an early marker of left ventricular dysfunction, be that systolic or diastolic. Longitudinal function of the left ventricle can be quantified with tissue velocity imaging (TVI), mitral annular plane systolic excursion (MAPSE) and global longitudinal strain (GLS), as measured by speckle-tracking. GLS measured by speckle-tracking is more technically challenging than measuring MAPSE and furthermore, in a setting with limited resources, not always widely available. Surprisingly, there is a paucity of data on the correlation of GLS to MAPSE. As GLS is the latest modality used to quantify longitudinal function of the LV and TVI is also more technically challenging than MAPSE, MAPSE was the chosen modality to compare to GLS. Furthermore, not all echocardiography systems are equipped for TVI and GLS, whereas that is not the case for MAPSE. MAPSE is therefore an easily acquired skill and widely available. Purpose of this study: To determine whether MAPSE, when compared to GLS, is an accurate way to quantify longitudinal function of the left ventricle. If this is shown to be the case, then MAPSE will be a proven, readlily available and easily acquired skill to detect cardiomyopathy, whether primary or secondary to a wide variety of systemic diseases. Methods: 175 patients who presented with a variety of primary cardiac diseases and/or systemic diseases with the potential for cardiac involvement were included into the study. 175 patients with normal cardiac function were also included into the study. Left ventricular longitudinal function of the left ventricle was quantified in each patient by means of MAPSE, as well as GLS measured by speckle-tracking. In order to correct MAPSE to body size, MAPSE:LV length was measured. The correlation of MAPSE with GLS was assessed by means of a two-by-two table. Results: In this group of 350 patients, split into 2 equal groups-175 with cardiomyopathy, either primary or secondary due to systemic disease, and 175 with no cardiomyopathy, the distinction is clear. The exposore, a GLS <−20% and a MAPSE:LV-lenghth <20% versus no exposure – a GLS <−20% and a MAPSE: LV-length >20% leads to a likelihood ratio of 485 (p=0) and a Pearson correlation of 525 (p=0) that impaired LV-longitudinal function is present. Conclusion: A MAPSE: LV-length <20% correlates reliably with an impaired GLS. This is a reliable substitute for GLS and for the general physician who screens for early cardiomyopathy this is a skill that will be cheaper and more easily learned than GLS. Funding Acknowledgement: Type of funding sources: None.